Pembelajaran Anak Usia 4-6 Tahun pada Masa Pandemi Covid-19 - Saumi Silviana Nur; Nurhasanah Nurhasanah; Baik Nilawati Astini; Fahruddin Fahruddin (Indonesian Publication Center, 2021)
This research was motivated by the Covid-19 Pandemic which requires learning from home. The purpose of this study was to see how children aged 4-6 years of age learned during the Covid-19 pandemic in Giri Madia Village, Lingsar District, West Lombok Regency. This research is qualitative research with a case study approach. The subjects of this study were 40 parents of children aged 4-6 years in Giri Madia Village, Lingsar District, West Lombok Regency. Data were collected through questionnaires and documentation. The data analysis used is descriptive qualitative analysis. The result showed that the learning of children 4-6 years old during the covid-19 pandemic was deemed less effective for parents, this was evidenced by the results of a survey which showed the mani obstacles faced by parents where one of the biggest obstacles for parents lies in the cost with the survey results of 100% strongly agree (SS. Parents stated that during learning from home their expenses increased because they had to buy quotas for each month. Therefore, the biggest hope for parents is that the pandemic can end soon and children return to school as usual, as the survey results obtained, which is 100% strongly agree (SS).